The Role of Financial Ratios in Predicting Return on Equity of Commercial Banks - Shiva Raj Poudel,; Subhadra Dahal,; Rishikesh Panthi, (Pravaha, 2022)
The explanatory power of the bank specific financial ratios on return on equity of the joint venture commercial banks operated in Nepal has been examined by using the database of 15 years from 2005/06 to 2019/20. The descriptive and correlational research design have been adopted for the study. The explanatory financial ratios used for the study includes capital adequacy, non-performing loan to total loan, net interest to total assets ratio, deposit to total assets ratio, and investment to total assets ratio. Statistical tools such as descriptive statistics, correlation analysis, and the regression analysis have been used as the major tools of data analysis. The results revealed that capital adequacy ratio, net interest to assets ratio and investment to assets ratio have the significant positive impact on commercial banks profitability. In contrast, non-preforming loan to total loan has the significant negative impact on banks' profitability whereas, deposit to total assets ratio has no significant impact on commercial banks' profitability.